2018
DOI: 10.1038/s41590-018-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Rfx7 limits metabolism of NK cells and promotes their maintenance and immunity

Abstract: Regulatory factor X 7 (Rfx7) is an uncharacterized transcription factor belonging to a family involved in ciliogenesis and immunity. Here, we found that deletion of Rfx7 leads to a decrease in natural killer (NK) cell maintenance and immunity in vivo. Genomic approaches showed that Rfx7 coordinated a transcriptional network controlling cell metabolism. Rfx7 NK lymphocytes presented increased size, granularity, proliferation, and energetic state, whereas genetic reduction of mTOR activity mitigated those defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 64 publications
1
51
0
Order By: Relevance
“…NK cells also undergo functional exhaustion during chronic inflammation [131] and may contribute to clinical responses following PD-1 blockade [132,•133] [136] also appear to be highly relevant checkpoint receptors in NK cell functional exhaustion. Furthermore, a wealth of new studies indicate the metabolism stringently regulates the function of NK cells [137][138][139][140][141][142][143], which can limit their antiviral capacity in the context of CMV or HCV infection [144,•145].…”
Section: Nk Cell Exhaustionmentioning
confidence: 99%
“…NK cells also undergo functional exhaustion during chronic inflammation [131] and may contribute to clinical responses following PD-1 blockade [132,•133] [136] also appear to be highly relevant checkpoint receptors in NK cell functional exhaustion. Furthermore, a wealth of new studies indicate the metabolism stringently regulates the function of NK cells [137][138][139][140][141][142][143], which can limit their antiviral capacity in the context of CMV or HCV infection [144,•145].…”
Section: Nk Cell Exhaustionmentioning
confidence: 99%
“…We therefore examined the cells for signs of metabolic reprogramming. Scatter has been used as an indicator of metabolic alteration in NK cells (Castro et al, 2018) and we found that side scatter increased in NK cells from the livers of obese mice ( Figure 5a). NK cells use mTOR for nutrient sensing and it also has an important role in immune regulation (O'Brien and Finlay, 2019).…”
Section: Nk Cells In Obese Mice Are Metabolically Reprogrammedmentioning
confidence: 93%
“…However, well-established ciliogenic RFX factors ( Rfx1-4 ) were not downregulated in NRF2-null MEFs [ 10 , 58 , 101 ]. Instead, reductions were seen for Rfx5 and Rfx7 , but it is unclear whether this is related to ciliogenesis, as these factors are better known as immunity regulators [ 10 , 101 , 102 , 103 ]. Alternatively, NRF2 may act on ciliogenic genes not through other transcription factors, but directly.…”
Section: Nrf2 Upregulation Of Primary Cilia and Hh Signalingmentioning
confidence: 99%